Polystichum hastipinnum (subg. Haplopolystichum; Dryopteridaceae), a new cave fern from Guangdong, China - Tang, Guang-Da; Huang, Lin; Li, Jia-Yu; He, Zeng-Li; Zhang, Li-Bing (Phytotaxa, 2017)
A new species of Polystichum (subg. Haplopolystichum; Dryopteridaceae), P. hastipinnum, is described from a limestone cave in northern Guangdong, China. Polystichum hastipinnum is most similar to P. kwangtungense in having oblong pinnae, but the former has stipe and rachis scales denser, basalmost pair of pinnae hastate and with bases somewhat cordate, while the latter has stipe and rachis scales much sparser, basalmost pair of pinnae oblong and with bases cuneate.